2016
DOI: 10.3390/ijerph13040361
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Arsenic in Rice Cereal and Other Dietary Sources for Infants and Toddlers in the U.S.

Abstract: Currently, there are no set standards or quantitative guidelines available in the U.S. for arsenic levels in rice cereal, one of the most common first solid foods for infants. The objective of this study was to evaluate whether the detected levels of inorganic arsenic (Asi) in rice cereal in the U.S. market are safe for consumption by infants and toddlers. A risk assessment was conducted based on literature reviews of the reported Asi in rice cereal from the U.S. Food and Drug Administration’s (FDA) survey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 18 publications
1
32
0
3
Order By: Relevance
“…Recent research has shown that infant formulas, specifically rice-based infant food, contains arsenic which can be traced to the natural raw materials used for processing. 28,29 Currently, there is no guideline for arsenic content in baby food, including infant formulas, but the food industry has been advised to adhere to a 0.2 mg/kg arsenic level to ensure the safety of infants and young children. 29,30 Infant formulas derived from rice have been shown to contain arsenic, which potentially has health risks for infants due to long-term exposure starting at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that infant formulas, specifically rice-based infant food, contains arsenic which can be traced to the natural raw materials used for processing. 28,29 Currently, there is no guideline for arsenic content in baby food, including infant formulas, but the food industry has been advised to adhere to a 0.2 mg/kg arsenic level to ensure the safety of infants and young children. 29,30 Infant formulas derived from rice have been shown to contain arsenic, which potentially has health risks for infants due to long-term exposure starting at a young age.…”
Section: Discussionmentioning
confidence: 99%
“…The infant exposure associated with this action level can be put into the context of the RSC approach, with sources of exposure during this lifestage (approximately 6 months of age) being infant formula or breast milk, and baby foods containing fruits, vegetables or meats, as well as drinking water. This array of iAs exposures was compiled in a Monte Carlo analysis based upon rice cereal containing 91 ppb as a central estimate (range 23 to 283 ppb) and assuming one serving of rice cereal (4.5 tablespoons dry cereal) per day (Shibata et al, 2016). The analysis showed rice cereal to contribute 45% of a 6–8 month old’s iAs exposure for the median consumer (49% if using the FDA action level of 100 ppb), well above a target RSC of 20% as discussed above for juice (Fig.…”
Section: Prioritizing Opportunities For Interventionmentioning
confidence: 99%
“…2, two intervention choices to reduce the rice cereal exposure to an RSC of 20% are: a) setting the action level to 41 (rounded to 40) ppb and through research and best production practices achieving this goal over time (Zhao et al, 2010); b) in the meantime, risk communication and meal frequency advice which educates parents to utilize a variety of cold and hot infant foods while limiting the number of rice cereal meals to 2 meals/week. This is based upon rice cereal at the FDA action level and a 20.4 g meal size (Shibata et al, 2016). At this meal frequency, rice cereal at 100 ppb would contribute <20% of the aggregate iAs exposure in a 6 month old infant.…”
Section: Prioritizing Opportunities For Interventionmentioning
confidence: 99%
“…Kawasaki disease, the second leading cause of heart attacks in children under five years of age, primarily affects ethnic populations (i.e., Asian and Blacks), and its etiology continues to perplex researchers in the field [9]. Shibata et al, conducted a risk assessment using U.S. Food and Drug Administration (FDA)-identified arsenic levels in associated children’s dietary products (i.e., rice cereal) along with recommended daily intake rates for these products, determining some concern for chronic exposures to children in the U.S. [10]. In a study of 68 children in Arizona, Beamer et al, found associations between urinary levels of a secretory protein (i.e., CC16, a potential clinical biomarker for airway damage due to exposure to arsenic) and arsenic concentration in soil, water, house-dust and dust loadings [11].…”
Section: Articles In This Special Issuementioning
confidence: 99%